2019
DOI: 10.1002/nav.21831
|View full text |Cite
|
Sign up to set email alerts
|

Fire truck relocation during major incidents

Abstract: The effectiveness of a fire department is largely determined by its ability to respond to incidents in a timely manner. To do so, fire departments typically have fire stations spread evenly across the region, and dispatch the closest truck(s) whenever a new incident occurs. However, large gaps in coverage may arise in the case of a major incident that requires many nearby fire trucks over a long period of time, substantially increasing response times for emergencies that occur subsequently. We propose a heuris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Отже, в деяких з проаналізованих робіт [6,7] процес виникнення небезпечних подій та надзвичайних ситуацій у населених пунктах описується законом розподілу Пуассона. В окремих роботах [10,11] для прогнозування їх кількості застосовуються методи нейромережевого прогнозування, але вони мають достатньо низьку точність.…”
Section: аналіз літературних даних і постановка проблемиunclassified
“…Отже, в деяких з проаналізованих робіт [6,7] процес виникнення небезпечних подій та надзвичайних ситуацій у населених пунктах описується законом розподілу Пуассона. В окремих роботах [10,11] для прогнозування їх кількості застосовуються методи нейромережевого прогнозування, але вони мають достатньо низьку точність.…”
Section: аналіз літературних даних і постановка проблемиunclassified
“…Consequently, this makes it possible to use mathematical models based on the Poisson distribution law to describe the process of calls coming to the ERUs. The method proposed in [15] is designed to solve the problem of redistribution of forces and means, provided that the operational situation in the territory of a settlement changes. The specified method cannot be used to determine the required number of EVs in ERUs.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…According to the results of the literature review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], it has been found that the known methods for determining the number of EVs with the purpose of equipping ERUs and redeploying the available forces and means are developed mainly for million-plus cities. Such cities are characterized by a higher population density than other types of settlements, which is why the happening of hazardous events and emergencies on their territories is accompanied by a large number of victims and casualties.…”
Section: Development Of a Predictive Model For Determining The Numbermentioning
confidence: 99%